The Drill Method Filming in Improving Mental Retardation Students Self-Care Skills - Visca Rinanda Putri; Ahsan Romadlon Junaidi; Dimas Arif Dewantoro (Journal of ICSAR, 2021)
Intellectual limitations are among the reasons children have difficulty building one of them on tooth-scrubbing. It has been marked by an oddity problem in the lightweight t children, including the children with mild intellectual disability that will be researched. If not treated, the problem can lead to other oral infections. Management requires a proper method of help with the enjoyable media - the drill method of visiting videos. The study USES the design of the A-B-A single-subject research (SSR) method. Research shows a rise in mean levels of 66.6% on baseline, 1, to 83% on intervention conditions, but two goes down to 79.5% on the baseline. However, the tendency of stability to baseline’s condition is 100%, which means the data it finds is stable despite declining. Capitalization between baseline’s condition, 1 to intervention state is 0%. So the conclusion from the research is that an intervention of a drilling method with a video successfully affects the ability to brush a child’s teeth.